Walking Stability During Normal Walking and Its Association with Slip Intensity Among Individuals with Incomplete Spinal Cord Injury. Issue 3 (22nd February 2019) - Arora, Tarun; Musselman, Kristin E.; Lanovaz, Joel L.; Linassi, Gary; Arnold, Catherine; Milosavljevic, Stephan; Oates, Alison
Abstract : Background: Ambulatory individuals with incomplete spinal cord injury (iSCI) experience frequent falls suggesting impairments in their balance control. Individuals with iSCI are more stable during normal walking as compared to able‐bodied (AB) individuals; however, it is not known whether this increased stability helps prevent hazardous slips. Objective: To compare walking stability during normal walking between iSCI and AB individuals, and to study the association between stability during normal walking and the intensity of an unexpected slip perturbation. Design: Cross‐sectional. Setting: Biomechanics of Balance and Movement lab, University of Saskatchewan, Saskatoon. Participants: Twenty iSCI (15 men; age: M = 60.05, SD = 17.77 years) and 16 (12 men; age: M = 58.92, SD = 17.10 years) AB individuals. Methods: Stability measures during unperturbed walking at a self‐selected speed were collected from all the participants. Additionally, stability measures were also collected from 10 of the AB participants walking at a slower speed. An unexpected slip perturbation was recorded in all participants during a self‐selected speed trial and peak‐slip heel velocity post slip was recorded. Main Outcome Measurements: Measures of stability: ankle co‐contraction, required coefficient of friction, walking velocity, foot angle, anteroposterior margin of stability, percentage double support, step length, and step width were compared between iSCI, AB‐self selected, and AB‐slow walking groups. Associations between slip intensity, indicated by peak post‐slip heel velocity, and stability measures were also examined through correlation analysis. Results: Individuals with iSCI walked slower, took shorter steps, and spent a greater percentage of time in double support compared with AB individuals walking at a self‐selected pace ( P < .01). Slower walking velocity was correlated with slower post‐slip velocity in participants with iSCI ( P = .01) only. Conclusions: Individuals with iSCI walk with greater stability than AB individuals during unperturbed walking because of a lower self‐selected speed, which appears to reduce the intensity of an unexpected slip perturbation. Level of Evidence: III